Faktor-faktor yang Berpengaruh Terhadap Pendapatan Pengrajin Batu Bata di Desa Tulikup Kecamatan Gianyar Kabupaten Gianyar - Wardhana, Kadek Wahyu; Natha, I Ketut Suardhika (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Development of an industry is a policy to increase a more advanced economic growth gradually and evenly, to changes in the economy for the better. Increased industrial sector is one of the efforts in increasing jobs. The purpose of this research is to find out if working hours, productivity, and work experience affect the revenue brick craftsman. Research locations in the Tulikup Village, Gianyar District Gianyar Regency. Many samples taken in this study is 73 business units, with a simple random sampling method and multiple linear regression analysis techniques were used in this study. Based on the results of research conducted in the village of Tulikup, District Gianyar Regency Gianyar suggests that working hours, productivity and work experience positive and significant effect on labor income brick industry. Variations effect of working hours, productivity and work experience on labor income Tulikup bricks in the village of Gianyar Regency in Gianyar showed value of R Square = 0.773, which means 77.3% while the remaining 22.7% of models of other variables that affect and are not included in the study this.
Keywords: working hours; productivity; work experience; revenue